HEALTHY TOGETHER, HAPPY FOREVER: CONTROL HYPERTENSION, CHOLESTEROL, URIC ACID AND BLOOD SUGAR WITH A BALANCED LIFESTYLE - Tashya Dhela Maylinda; Linawaty Linawaty; Ria Anggraeni; Yacinta Paloma (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2026)
This community service activity aims to enhance public awareness and understanding of the prevention of non-communicable diseases, particularly hypertension, cholesterol disorders, uric acid imbalance, and diabetes, through the adoption of a balanced and healthy lifestyle. The program was carried out through interactive counseling sessions and basic health screenings involving the academic community and parents at Saint John Christian School. The intervention was designed to provide comprehensive information on risk factors, long-term health impacts, and practical lifestyle modifications that participants can implement in their daily routines. Evaluation of the activity was conducted using pre-test and post-test assessments, which were analyzed using the Wilcoxon test to measure knowledge improvement. The results showed a significant increase (p < 0.001), with the mean pre-test score of 41.95 rising to 83.90 after the intervention. These findings demonstrate that interactive educational approaches are effective in improving health literacy and encouraging participants to adopt balanced lifestyle habits as preventive measures against non-communicable diseases.